Rethinking on Expressive Speech Act Realization in The Comments Section on YouTube Channel - Apsari Javiera Hambali; Faizal Risdianto; Salsabila Shofia Rahma (UIN Salatiga, 2024)
Rethinking the realization of expressive speech acts in the comments section of YouTube channels offers an opportunity to delve deeper into the evolving dynamics of online communication and community engagement. This research explores expressive speech acts in One Direction's YouTube's comments section, examining how users express emotions, opinions, and reactions to video content. It explores new perspectives, emerging trends, and the ever-changing digital landscape of digital interactions. This research methodology is a descriptive qualitative method, and the data source was compiled from the comments section on One Direction's YouTube channel. Therefore, the researcher concludes there were seven types of expressive speech acts from fifty-one comments. There were 26 expressions of sorrow, four expressions of congratulating, two expressions of thanking, 13 expressions of praising, four expressions of happiness, and one expression for blaming and regretting. The most dominant expression used in the comments section on One Direction's YouTube Channel is the expression of sorrow. This expression appeared 26 times, out of 51 expression speech act listed. The researcher concludes that sorrow is the expression that is mainly used in the comments section.